SELF-CONTROL WHEN EXERCISING KICKBOXING SPORTS - Abdumutalipov Asilbek Bahodirovich (PEDAGOGS, 2024)
Abstract: Self-control is a form of control over the state of health, physical development and subjective and objective indicators of the state of the body engaged in physical exercises related to the sport of kickboxing, using simple and convenient techniques. The results of self-monitoring are considered an addition to the results of medical control. Self-control Helps students to identify the negative effects of exercise on the body in a timely manner.